Enhanced Immunogenicity and Affinity with A35R-Fc-Based Chimeric Protein Compared to MPXV A35R Protein - Shimeng Bai; Yanxin Cui; Qibin Liao; Hongyang Yi; Zhonghui Liao; Gengwei Zhang; Fenfang Wu; Hongzhou Lu (Viruses, 2025)
The re-emergence of the mpox pandemic poses considerable challenges to human health and societal development. There is an urgent need for effective prevention and treatment strategies against the mpox virus (MPXV). In this study, we focused on the A35R protein and created a chimeric A35R-Fc protein by fusing the Fc region of IgG to its C-terminal. We then assessed its reactivity with A35R-specific antibodies and human convalescent plasma, as well as its immunogenicity. Our findings indicate that the A35R-Fc protein significantly enhances affinity to A35R antibodies compared to the commercially available A35R protein and exhibits considerable reactivity to human plasma. Additionally, mice immunized with A35R-Fc exhibited increased neutralizing antibody titers against the live MPXV. These results support the potential of Fc domain chimeric antigens as a strategy to enhance the efficacy of subunit vaccines targeting the MPXV.